Synthesis of silver nanoparticles in an aqueous suspension of graphene oxide sheets and its antimicrobial activity - Das, Manash R.; Sarma, Rupak K.; Saikia, Ratul; Kale, Vinayak S.; Shelke, Manjusha V.; Sengupta, Pinaki (Colloids and Surfaces B-Biointerfaces, 2011)
A solution-based approach to the synthesis of silver (Ag) nanoparticles by chemical reduction of AgNO3 in a graphene oxide (GrO) suspension is demonstrated. X-ray diffraction and transmission electron microscopy indicate that the Ag nanoparticles, of size range 5-25 nm, were decorated on the GrO sheets. The size and shape of the Ag nanoparticles are dependent on the concentration of the AgNO3 solution. Antimicrobial activity of such hybrids materials is investigated against the Gram negative bacteria Escherichia coli and Pseudomonous aeruginosa. The bacterial growth kinetics was monitored in nutrient broth supplemented with the Ag nanoparticle-GrO suspension at different conditions. It was observed that P. aeruginosa is comparatively more sensitive to the Ag nanoparticle-GrO suspension. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Antimicrobial activity; Escherichia coli; graphene oxide; Pseudomonous aeruginosa; Silver nanoparticle